Essence of hawker centres in Singapore - Tan, Ee Jing (Nanyang Technological University, 2023)
Singapore is renowned as a food haven, largely due to our hawker foods. However, with the city-state's rapid digitalisation and growth, it has become increasingly challenging to preserve the traditional hawker culture. Consequently, it is likely that hawker centres in Singapore will undergo significant changes, and the cultural landscape of hawker culture will inevitably shift in the near future. To combat this, this project’s main objective will be to archive and document hawker centres through the eyes of locals, with the aim of preserving the rich culture that these hawker centres embody.